The STING/TBK1/IRF3/IFN type I pathway is defective in cystic fibrosis - Occhigrossi, Luca; Rossin, Federica; Villella, Valeria Rachela; Esposito, Speranza; Abbate, Carlo; D’Eletto, Manuela; Farrace, Maria Grazia; Tosco, Antonella; Nardacci, Roberta; Fimia, Gian Maria; Raia, Valeria; Piacentini, Mauro (Frontiers in Immunology, 2023)
Cystic fibrosis (CF) is a rare autosomal recessive disease caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. The most common mutation is F508del-CFTR (ΔF) which leads the encoded ion channel towards misfolding and premature degradation. The disease is characterized by chronic bronchopulmonary obstruction, inflammation and airways colonization by bacteria, which are the major cause of morbidity and mortality. The STING pathway is the main signaling route activated in the presence of both self and pathogen DNA, leading to Type I Interferon (IFN I) production and the innate immune response. In this study, we show for the first time the relationship existing in CF between resistant and recurrent opportunistic infections by Pseudomonas aeruginosa and the innate immunity impairment. We demonstrate through ex vivo and in vivo experiments that the pathway is inadequately activated in ΔF condition and the use of direct STING agonists, as 2′,3′-cyclic GMP-AMP (2’, 3’ cGAMP), is able to restore the immune response against bacterial colonization. Indeed, upon treatment with the STING pathway agonists, we found a reduction of colony forming units (CFUs) consequent to IFN-β enhanced production in Pseudomonas aeruginosa infected bone marrow derived macrophages and lung tissues from mice affected by Cystic Fibrosis. Importantly, we also verified that the impairment detected in the primary PBMCs obtained from ΔF patients can be corrected by 2’, 3’ cGAMP. Our work indicates that the cGAS/STING pathway integrity is crucial in the Cystic Fibrosis response against pathogens and that the restoration of the pathway by 2’, 3’ cGAMP could be exploited as a possible new target for the symptomatic treatment of the disease.